Impact of fly ash impurity on the hydrate-based gas separation process for carbon dioxide capture from a flue gas mixture - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2014)
The hydrate-based gas separation (HBGS) process for gas mixtures of CO2 + N-2 (flue gas) and CO2 + H-2 (fuel gas) has proven to be very efficient and highly selective for CO2 capture. In addition to CO2 and N-2, flue gas from coal-based thermal power stations can contain impurities such as nitrogen oxides (NOx), sulfur oxides (SOx), and fly ash. In this work, the impact of fly ash on the HBGS process efficiency was investigated. Tetrahydrofuran (THF, 1 mol %) was used as a thermodynamic promoter, and sodium dodecyl sulfate (SDS) and sodium dodecyl benzenesulfonate (SDBS) (anionic surfactants) were used as kinetic promoters. Whereas the use of THF in the HBGS process reduces the operating pressure significantly, both SDS and SDBS were found to enhance the rate of hydrate formation. It was observed that the hydrate equilibrium conditions did not change in the presence of fly ash. However, the presence of fly ash enhanced the separation efficiency of the HBGS process by reducing the induction time and increasing the kinetics of hydrate formation. Therefore, the presence of fly ash in a flue gas mixture is not detrimental to the HBGS process, which is a positive factor for the capture and geological sequestration of CO2 in the form of gas hydrates.